Performance and Characterization of Alsi10mg as Additive Base Material - Vinayak Wagmare; Sandeep Mashetty (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Additively manufactured also pertained to as 3D printing relates to the technologies that construct a three- dimensional device by adding raw material subcaste- by- subcaste consistent with CAD. AM is critical for no tooling to deliver a working part. This system is achievable for constructing parts of the compound configuration that are generally highly impossible to be manufactured by the conventional manufacturing operation. In the current work AlSi10Mg powder was used to build SLM parts according to various ASTM standards and were tested for microstructure, mechanical and wear properties. SEM was used to analysis surface morphology, fracture, and wear morphology. Overall, Additively created techniques focus on engineering metals from the perspective of the machine-driven solid products of the components, making it possible to employ them as widely as possible. Findings proven that the effects of addition of Si and Mg on the progression of the stage structure and microstructure of aluminum alloy produced using additive manufacturing were examined. AlSi10Mg that has undergone selective laser melting might also have comparable Wear resistance to conventional processes. Additive manufacturing is a growing field of engineering that allows us to produce complex goods without the use of conventional industrial course development.
Keywords: AM Process; SLM; Hardness; Fractography; Wear